PENGARUH PROMOSI , CITRA KOPERASI , DAN KUALITAS PELAYANAN TERHADAP PENINGKATAN JUMLAH ANGGOTA PADA KOPERASI SIMPAN PINJAM - Isrok Isrok; Yanthi Metri Gunawan; Siti Asriah Immawati (Universitas Muhammadiyah Tangerang, 2021)
The purpose of this study was to determine the effect of promotion, the image of cooperatives, and service quality on increasing the number of members in savings and loan cooperatives (a case study of savings and loan cooperatives in Tangerang Regency). With an Associative Quantitative approach. The data analysis method used multiple regression. All populations in this study will be a sample, namely as many as 63 samples. The results of the research are (1) promotion has a significant positive effect on increasing the number of cooperative members (2) the image of the cooperative has no significant negative effect on the increase in the number of cooperative members (3) service quality has a significant and positive effect on increasing the number of cooperative members (4) promotion, the image of the cooperative, the quality of service simultaneously affected the increase in the number of cooperative members by F count 12,551> F table 1.99. The result of the coefficient of determination test showed that the value of Adjusted R Square was 35.9% and the remaining 64.1% was influenced by factors other than the variables examined in this study.Keywords: Promosi , Citra Koperasi , Kualitas Pelayanan, Peningkatan Jumlah Anggota